Microwave spin resonance investigation on the effect of the post-processing annealing of CoFe2O4 nanoparticles. Issue 5 (21st April 2020) - Kumar, Prashant; Pathak, Saurabh; Singh, Arjun; Khanduri, H.; Basheed, G. A.; Wang, Lan; Pant, R. P.
Abstract : A novel investigation on the finite-size effects on the spin resonance properties of cobalt ferrite (CoFe2 O4 ) nanoparticles has been performed using a room temperature ferromagnetic resonance (FMR) technique. Abstract : A novel investigation on the finite-size effects on the spin resonance properties of cobalt ferrite (CoFe2 O4 ) nanoparticles has been performed using a room temperature ferromagnetic resonance (FMR) technique. A single broad spectrum was obtained for the CoFe2 O4 nanoparticle samples, which indicated that all the samples were showing ferromagnetic characteristics. An asymmetric FMR line shape with a hefty trailing section was obtained due to the high magneto-crystalline anisotropy in CoFe2 O4 nanoparticles, which changed with the size distribution. The resonance field for the samples shifted to a higher value due to the increase in the magneto-crystalline anisotropy in the CoFe2 O4 nanoparticles with an increase in size. A systematic change in the resonance field and line width was observed with the change in the size distribution of the particles. Initially, it decreased with an increase in the size of the particles and increased after the critical size range. The critical size range is the imprint of the shift of the magnetic domain from a single domain to multi domain. The line width increased at higher annealing temperatures due to the enhancement in the dipole–dipole interaction, which led to a higher spin concentration as well as magneto-crystalline anisotropy. Furthermore, the saturation magnetization ( M s ) as well as ' M r / M s ' increased from 37.7 to 71.4 emu g −1 and 0.06 to 0.31, respectively. The highest coercivity (750.9 Oe) and anisotropy constant (4.62 × 10 4 erg cm −3 ) were found for the sample annealed at 700 °C, which can be corroborated by the literature as the critical annealing temperature at which CoFe2 O4 nanoparticles shift from single domain nanoparticles to multi-domain nanoparticles. Post-processing annealing is critical in advanced processing techniques and spin dynamics plays a vital role in various interdisciplinary areas of applications.